2018
DOI: 10.1002/jsfa.8922
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dominance of sensations and preferences of Brazilians and Slovakians: A cross‐cultural study of cachaças stored with woods from the Amazon rainforest

Abstract: Brazilians preferred cachaça stored with oak wood, and Slovakians preferred cachaça stored with JT wood, with acceptability being strongly associated with the dominance of wood flavor and vanilla attributes at the end of the evaluation time. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Peptidic sensors were used in a study to predict the identity of unknown cachaça extracts and discriminate Cabernet Sauvignon wines based on grape maturation time [144]. Simioni et al [145] evaluated the acceptability of cachaça stored in different woods among Brazilian and Slovakian consumers. The study found that while Brazilians preferred cachaça stored with oak, Slovakians preferred those stored with different woods.…”
Section: Distinguishing Cachaça From Rum: Pattern Recognition Methodsmentioning
confidence: 99%
“…Peptidic sensors were used in a study to predict the identity of unknown cachaça extracts and discriminate Cabernet Sauvignon wines based on grape maturation time [144]. Simioni et al [145] evaluated the acceptability of cachaça stored in different woods among Brazilian and Slovakian consumers. The study found that while Brazilians preferred cachaça stored with oak, Slovakians preferred those stored with different woods.…”
Section: Distinguishing Cachaça From Rum: Pattern Recognition Methodsmentioning
confidence: 99%
“…Quando dividimos esse consumo entre os tipos de bebida alcoólica, as bebidas destiladas aparecem em primeiro lugar no mundo, com 44,8% do consumo, seguido da cerveja, com 34,3%, e do vinho, com 11,7% (OMS, 2018), sendo a Europa a primeira colocada em consumo de destilados (SIMIONI et al, 2018).…”
Section: Lista De Ilustraçõesunclassified